Saliva and Plasma Neutralizing Activity Induced by the Administration of a Third bnt162b2 Vaccine Dose - Garziano, Micaela; Utyro, Olga; Strizzi, Sergio; Vanetti, Claudia; Saulle, Irma; Conforti, Chiara; Cicilano, Federica; Ardizzone, Francesco; Cappelletti, Gioia; Clerici, Mario; Limanaqi, Fiona; Biasin, Mara (International journal of molecular sciences, 2022)
The BNT162b2 vaccine induces neutralizing activity (NA) in serum, but no data are available on whether a third-dose activates specific-immunity within the oral mucosa, representing the primary route of viral-entry. To carefully address this issue, we investigated if such immunity is boosted by SARS-CoV-2-infection; how long it is maintained over-time; and if it protects against the SARS-CoV-2 lineage B.1 (EU) and the emerging Delta and Omicron variants. NA was measured in plasma and saliva samples from: uninfected SARS-CoV-2-Vaccinated (SV), subjects infected prior to vaccination (SIV), and subjects who were infected after the second (SIV2) or the third (SIV3) vaccine dose. Samples were collected immediately before (T0), 15 days (T1), and 90 days (T2) post third-dose administration (SV and SIV), or 15 days post-infection (SIV2 and SIV3). In all the enrolled groups, NA in plasma and saliva: (i) was higher against EU compared to the other variants at all time-points (SV: T0 and T1, EU vs. both Delta and Omicron p < 0.001; T2 p < 0.01) (SIV: T0, EU vs. Delta p < 0.05; EU vs. Omi p < 0.01; T1 and T2 EU vs. Delta p < 0.01; EU vs. Omi p < 0.001); (ii) was boosted by the administration of the third dose; iii) declined over-time, albeit being detectable in almost all subjects at T2. The monitoring of NA over time will be important in clarifying if different NA levels may influence either acquisition or course of infection to properly plan the timing of a fourth vaccine dose administration.